2020
DOI: 10.1007/s00415-020-09847-8
|View full text |Cite
|
Sign up to set email alerts
|

Treatment expectations and patient-reported outcomes of nusinersen therapy in adult spinal muscular atrophy

Abstract: Background The antisense-oligonucleotide (ASO) nusinersen has recently been approved as the first genetically modifying therapy for 5q-associated spinal muscular atrophy (SMA) based on randomized sham-controlled trials in infants and children. The efficacy in adults with long disease history and advanced disease status is still widely unknown; the same applies to specific expectations of adult SMA patients and to what extent they are met and may impact outcome measures. Methods In a longitudinal monocentric st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 31 publications
4
40
0
Order By: Relevance
“…Besides improvement in muscle strength, SMA patients considered mobility, endurance, and disease stabilization as relevant treatment outcomes in a previous study. 32 Early high treatment satisfaction could therefore already arise from the interruption of further disease progression. As TSQM-1.4 © lacks qualitative analyses, the exact causes underlying patients’ satisfaction with effectiveness remain to be further elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Besides improvement in muscle strength, SMA patients considered mobility, endurance, and disease stabilization as relevant treatment outcomes in a previous study. 32 Early high treatment satisfaction could therefore already arise from the interruption of further disease progression. As TSQM-1.4 © lacks qualitative analyses, the exact causes underlying patients’ satisfaction with effectiveness remain to be further elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing patients repeatedly reporting wearing-off to those with no experienced diminishing effects, the BMI was significantly higher in patients with wearing-off phenomena. Interestingly, in a previous study, we already identified that patients with a higher BMI more frequently reported a deterioration of symptoms during the treatment course [ 21 ]. Higher BMI, however, is not associated to an increased CSF volume [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…SMA patients ( n = 51) with genetically confirmed mutations in the SMN1 gene were screened between 16 May 2017 and 15 October 2019 at both sites and ALS patients ( n = 67) between 23 April 2015 and 13 June 2018 at MHH only. All enrolled SMA patients received therapy with the antisense oligonucleotide nusinersen [ 26 , 27 ]. Inclusion criteria for all patients were age ≥ 18 years and ability to perform cognitive function testing in a structured personal interview.…”
Section: Methodsmentioning
confidence: 99%